2000
DOI: 10.1046/j.1365-2249.2000.01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Th1- and Th2-derived cytokines in serum are elevated in Graves' ophthalmopathy

Abstract: Increased serum cytokine levels have been reported in patients with autoimmune thyroid disease, but less is known about their levels in patients with Graves' ophthalmopathy (GO). It is not known whether GO is a cell‐mediated or humoral autoimmune disease. We investigated whether serum cytokines are elevated in GO patients and whether the cytokines were Th1‐ or Th2‐derived. In addition, elevated cytokines might reflect the activity of GO, and thus we investigated whether cytokine levels could predict the clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 45 publications
7
42
1
1
Order By: Relevance
“…Wahrenberg et al (24) have reported that adipose tissues from these individuals release several-fold higher levels of IL-6 than do similar tissues from control subjects. Circulating IL-6 levels have also been found to be elevated in Graves' disease (17)(18)(19)(20)(21)(22). Moreover, treatment of thyrotoxicosis fails to normalize these levels, suggesting strongly that they are a consequence of the underlying autoimmune process.…”
Section: Discussionmentioning
confidence: 99%
“…Wahrenberg et al (24) have reported that adipose tissues from these individuals release several-fold higher levels of IL-6 than do similar tissues from control subjects. Circulating IL-6 levels have also been found to be elevated in Graves' disease (17)(18)(19)(20)(21)(22). Moreover, treatment of thyrotoxicosis fails to normalize these levels, suggesting strongly that they are a consequence of the underlying autoimmune process.…”
Section: Discussionmentioning
confidence: 99%
“…A major difference between active and inactive GO is the presence of a lymphocytic infiltrate in orbital tissues (161,162). Thus, the increased production of CXCL10 might be sustained by orbital lymphocytes.…”
Section: Cxcr3-binding Chemokines In Gomentioning
confidence: 99%
“…In addition, 210 Neuroimmunomodulation 2004;11:209-213 Phenekos/Vryonidou/Gritzapis/Baxevanis/ Goula/Papamichail cytokines potentiate the expression of both major histocompatibility complex class I and II molecules by thyroid follicular cells and upregulate expression of adhesion and complement regulatory molecules [11][12][13][14]. Cytokines have also been implicated in the pathogenesis of thyroidassociated ophthalmopathy by inducing fibroblast proliferation and increased production of glycosaminoglycans, resulting in eye muscle and orbital tissue fat enlargement [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%